Geomorfologia das confluências do alto curso do rio Paraná, um estudo dos rios: Ivaí-PR, Piquiri-PR e Ivinhema-MS - Grzegorczyk, Vanderlei (2016)
In Brazil, water studies have grown in recent decades. Stands out the research conducted by the Group for Multidisciplinary Studies on the Environment - Gema, in the upper Paraná River. Few studies address the subject river confluence. This research investigates the confluence of the Ivinhema-MS River, Ivaí-PR River and Piquiri-PR River, with the Paraná River, located on the stretch between Porto Primavera Reservoir and the Itaipu Lake. This study aimed to understand the processes of geomorphological construction of the confluence areas, through the analysis of flows, sediment dynamics, geometry of the channels at the confluences and their contribution to the Paraná River channel. Knowledge of the dynamics of confluences is critical to environmental and fluvial studies and their interrelationship with the plain. They are characterized as very complex environments, where there is the combination of matter (water, sediment) and energy (forces exerted by flows) from different sources beyond ecological exchange between the river systems. The study area was delimited by means of remote sensing, aerial photographs and topographic maps and constructing a database in the Geographic Information System (GIS). For the analysis of the flow velocity and flow rate, it was used ADCP (Acoustic Doppler Current Profiler) and the echo sounder to survey and construct bathymetric and geomorphological maps. For suspended load analysis, we used a vertically integrated collector, for quantification of data, and applied the formula QSS = 0.0864.Q.CSS (CARVALHO, 1994). For collection of bottom load, we used a manual and punctual sampler, like Van Vem. For the dominant flow, we used the formula De Serres et al. (1999), as follows: Mc = U Trib. Q Trib / U Channel. We performed a literature review including texts, books and articles, data from fluviometric and rain gauge stations. The confluences studied showed the scour area, stagnation, flow acceleration zones, vortices and flow recovery area. Deflation zone only occurred in the confluences of Piquiri-PR and Ivaí-PR rivers. The confluence angle is considered important in dynamics surrounding this area, but it was less relevant in the direction of the scour area than in the direction of the tributary thalweg. The angle of the confluences were 81.3º in the Piquiri-PR River, 56º in the Ivaí-PR River, and at the confluence Ivinhema 01, 02 and 03, values were, respectively, 68.5º; 40; and 44.8º, being asymmetric. The widening of the tributary at confluences occurred only in Ivaí-PR and Piquiri-PR rivers, and was inexpressible at confluences of the the Ivinhema-MS River. The Ivaí-PR and Piquiri-PR rivers, at their lower reaches, flow over a rocky bottom; the Ivinhema-MS River, over deposits of the Paraná River plain, more prone to erosion. The amount of suspended load was higher in the Ivaí-PR River, followed by Ivinhema-MS River, and the lowest value was found in the Piquiri-PR River. The predominant bottom load consisted of fine and medium-sized sand in the confluences. Bars attributed to forces acting at the confluence took place in the Ivaí-PR River, one at the mouth and one upstream, this by the reverse flow in flood periods of the tributary; this was the only tributary controlling the flow during the study. The tributaries contributed with 10%, on average, to the flow rate of the secondary channel of the Paraná River, only the Ivaí-PR River can exceed 50% in flood periods .